Peran Literasi Keuangan dalam Meningkatkan Kesejahteraan Keluarga Melalui Pengelolaan Keuangan yang Bijak - Lyandra Aisyah Margie; Purwatiningsih Purwatiningsih; Silvia Sari (Jurnal PKM Manajemen Bisnis, 2026)
This community service activity aims to improve the financial literacy of housewives in managing household finances wisely in order to enhance family welfare. The main problems faced by the community include low financial knowledge, lack of cash flow recording habits, consumptive behavior, and dependence on informal loans. This activity was conducted in RW 01, Cinangka Village, Sawangan District, Depok City, involving 20 housewives as participants. The methods used were counseling, training, and mentoring through direct interaction. The materials covered basic financial management, budgeting, income and expenditure recording, debt management, as well as emergency fund and basic investment planning. The results indicate an improvement in participants’ understanding and awareness of the importance of financial literacy, along with their ability to prepare and implement simple household financial records. In addition, there was a positive change in participants’ mindset in distinguishing between needs and wants, as well as in making financial decisions. Therefore, this activity contributes to strengthening family economic resilience and promoting sustainable household welfare.